Analisis Senyawa Obat Vankomisin dalam Plasma Darah dengan Berbagai Metode - Elvira Julia elvira julia; Arline Rahmadianti Kusumawardhani; Anggraini Anggraini; Nolla Olipia Elva Megrian; Marsah Rahmawati Utami; Lina Nurfadhila (Journal of Pharmaceutical and Sciences, 2023)
Vancomycin is one of antibiotic that used to treat infections caused by methicillin-resistant Staphylococcus aureus (MRSA). The recommended concentration for vancomycin is 15-20 mg/L every 8-12 hours in the blood. Vancomycin has a narrow therapeutic index so that small changes in dose can lead to significant changes in drug response. Therefore, monitoring of drug therapy is recommended to optimize vancomycin concentrations. Vancomycin levels in blood plasma have been measured using a variety of analytical techniques, the two that are most frequently employed are high performance liquid chromatography (HPLC) and immunoassay methods. This review intends to give information on the two analytical methods and what is appropriate to learn about the comparison of the two analytical methods on vancomycin levels in blood plasma. The results of the review that has been carried out are that the main difference between the HPLC method and the immunoassay is in the basic principles of the analytical technique. The immunoassay method (FPIA and RIA methods) is more appropriate to use than the HPLC method because it conforms the results of the analysis, especially in the range of concentrations and sensitivities obtained.